FRI0532 SONIC HEDGEHOG PROMOTES PROLIFERATION, MIGRATION AND INVASION OF FIBROBLAST-LIKE SYNOVIOCYTES IN RHEUMATOID ARTHRITIS VIA P38-MAPK SIGNALING. (June 2019) - Zhu, Shangling; Shi, Yiming; Ye, Yuanmei; Feng, Xiaoxue; Huang, Jianlin
Abstract : Background: Abnormal activation of Sonic hedgehog (Shh) signaling has been found in synovium from patients with rheumatoid arthritis and inhibition of Shh signaling pathway suppresses the proliferation and migration of fibroblast-like synoviocytes in rheumatoid arthritis (RA-FLS). However, the mechanism how Shh signaling promotes tumor-like behavior of RA-FLS is not well elucidated. Objectives: In this study, we aimed to investigate the effect of Shh on p38 MAP kinase signaling and hypothesized that Shh promotes proliferation, migration and invasion of RA-FLS via p38-MAPK signaling. Methods: Cultured RA-FLSs were treated with Smoothened agonist (SAG) or IL-1β combined with Smoothened antagonist (Cyclopamine). The levels of phosphorylation of p38, its upstream kinases including TGFβ activated kinase 1 (TAK1), MKK3, MKK6 and downstream target MAPKAPK2 (MK-2) were determined by western blot. The functional state of p38 was determined using in vitro kinase assay. Cell proliferation was evaluated by Cell Counting Kit -8 assay. Cell migration and invasion were performed by Transwell assay. The expression of matrix metalloproteinase proteins (MMPs), IL-6 and IL-8 was examined by real-time PCR. Results: SAG rapidly increased phosphorylation of p38, TAK1, MKK3, MKK6 and MK2 in RA-FLS and combination of SAG and p38 inhibitor significantly decreased the phosphorylation of these kinases ( P <0.01). Inhibition of Shh significantly decreased the levels of phosphorylation of p38, TAK1, MKK3, MKK6 and MK2 in IL-1β stimulated RA-FLS ( P <0.05). In vitro kinase assay showed that stimulation of SAG significantly increased the kinase activity, and the kinase activity was inhibited by p38 inhibitor. Furthermore, SAG increased cell proliferation, migration, invasion and production of MMP1, MMP3, MMP13, IL-6 and IL-8. However, these enhanced activities of RA-FLS were inhibited in the presence of p38 inhibitor. Conclusion: The study indicates that Shh is associated with activation of p38 MAPK signaling in RA-FLS and Shh may promote the tumor-like behavior of RA-FLS via p38 signaling. Acknowledgement: This work was supported by grants from the National Natural Science Foundation of China (81571584, 81701609). Disclosure of Interests: None declared